RANCANG BANGUN SISTEM INFORMASI TERINTEGRASI PRESENSI BERBASIS QR CODE DAN GEOTAGGING UNTUK PENGGAJIAN PADA MTS NURUL MUBTADIIN - faridatun; Hari Lugis Purwanto; Rini Agustina (Department of System Information, 2026)
Abstract. Attendance recording and teacher payroll management at MTs Nurul Mubtadiin currently face significant challenges due to the use of manual paper-based journals, leading to high risks of attendance fraud, data loss, and significant inaccuracies in monthly salary calculations. This research aims to design and build an integrated information system that utilizes QR Code technology and Geotagging to ensure data validity and administrative efficiency. The system development adheres to the Waterfall methodology, covering requirements analysis, system design, implementation, and rigorous testing phases. Developed using PHP and MySQL, the system integrates attendance logs directly with a payroll module, providing real-time data for automated salary disbursement. System validation was performed via User Acceptance Testing (UAT) involving 25 respondents, yielding an average feasibility score of 94.25%, which falls into the